Beyond the Phi factor: Correction of experimental data for vaporization in tempered reactions for pressure‐relief system design. Issue 2 (30th July 2014) - Zhao, Guibing
<x xml:space="preserve">Abstract</x> Design of emergency relief systems to accommodate runaway reactions often requires using bench‐scale adiabatic calorimeters to evaluate thermokinetic data of a full‐scale reactor. However, the well‐known method to correct bench‐scale experimental data for "thermal inertia"—the Phi factor—does not consider the effect of vaporization on thermokinetic data. Calorimeter volumetric fill ratio is an important parameter directly relating to the vaporization effect and is discussed in this article. For a 60% fill ratio, a case study of an aqueous reaction system shows that the measured reaction heat would be 7% less than the actual value for a reaction with a heat release of 800 J/g, 5% less than the actual value with a heat release of 600 J/g, and 2% less than the actual value with a heat release of 300 J/g. The temperature rise rate is even more sensitive to the fill ratio. A high fill ratio is desirable, to get more‐accurate temperature rise data for a tempered exothermic reaction. A low fill ratio requires a significant Phi correction and could also give a misleading thermokinetic interpretation of a plant‐scale reactor. Applying the same fill ratio of a plant‐scale reactor to tests in an adiabatic calorimeter—to get thermokinetic data for emergency relief sizing—is recommended. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 130–136, 2015